2022
DOI: 10.1016/j.clml.2021.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Hypomethylating Agents for Management of Myelodysplastic Syndromes: Patients’ Perspectives on Treatment

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…30 A recent survey study assessed the experiences and challenges of IV/SC HMA use for MDS patients or their caregiver proxies. 32 Almost all of the 141 respondents in the study received treatment in a medical facility, and 43% traveled for 1 hour or more for treatment. Approximately 44% of patients reported experiencing a treatment delay; reasons varied but common reasons included not having time off work, and not having someone to accompany them or drive them to the treatment center.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 A recent survey study assessed the experiences and challenges of IV/SC HMA use for MDS patients or their caregiver proxies. 32 Almost all of the 141 respondents in the study received treatment in a medical facility, and 43% traveled for 1 hour or more for treatment. Approximately 44% of patients reported experiencing a treatment delay; reasons varied but common reasons included not having time off work, and not having someone to accompany them or drive them to the treatment center.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 44% of patients reported experiencing a treatment delay; reasons varied but common reasons included not having time off work, and not having someone to accompany them or drive them to the treatment center. 32 Therefore, it is possible that, in some patients, discontinuation was due to practical and logistical challenges associated with the need to receive multiple consecutive HMA treatment cycles administered in a hospital or other treatment facility. 18 , 20 , 30 In the unadjusted analyses in our study, patients who discontinued HMA before 4 cycles were more likely to be single single/separated/divorced/widowed than those who continued therapy for ≥ 4 cycles, suggesting the possibility that this group may need more support in traveling to the treatment center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our other research, we also found that patients with MDS reported that treatment interferes with their regular daily activities, is not convenient and that financial barriers created delays and/or discontinuation of treatment. 47 This in turn has clinical and economic consequences, as a longer duration of HMA therapy may be associated with better overall survival outcomes 44 and the failure of HMA treatment is associated with increased healthcare burden. 45 , 13 , 46 The proportion of respondents predicted to choose an oral treatment option, when offered alongside other options, was > 75%.…”
Section: Hesitancy or [Feel] Guilty About Asking Questions Or Seeking...mentioning
confidence: 99%
“…This is consistent with the percentage of patients indicating they would prefer oral MDS treatment to IV/SC therapies (69%) reported in the treatment burden survey of MDS patients. 47 This suggests that up to 30% of patients may prefer to remain on IV/SC. This is not entirely surprising, as some patients may face few difficulties with treatment administration and may value the interaction with staff at the clinic.…”
Section: Hesitancy or [Feel] Guilty About Asking Questions Or Seeking...mentioning
confidence: 99%